IMPLEMENTASI MANAJEMEN PENDIDIKAN DALAM PENGELOLAAN PROGRAM TEACHING FACTORY KOLABORASI DI SMK MUHAMMADIYAH 2 PEKANBARU - Anti, Ardianti; Marhadi, Hendri; Nur Mustafa, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teaching Factory (TEFA) is a production- or workplace-based learning model that aims to integrate the educational process in vocational high schools (SMK) with real conditions in the industrial world. This study aims to analyze the implementation of educational management in managing the collaborative Teaching Factory program at SMK Muhammadiyah 2 Pekanbaru using a SWOT analysis approach.The method used is a qualitative descriptive approach by analyzing TEFA work program documents and their management practices in the school. The results of the study show that the management of the Teaching Factory program has implemented educational management functions, including planning, organizing, implementation, and evaluation.The SWOT analysis indicates that this program has strengths in cross-departmental involvement, students’ real-world experience, systematic management, industrial partnerships, and economically valuable products. Its weaknesses lie in the suboptimal involvement of industry and the uneven ability of students to operate production equipment. Opportunities include high demand for creative products, potential industrial collaboration, and digital marketing. Meanwhile, threats include competition from external industries, rapid technological development, and changing market demands that require continuous innovation.Therefore, strengthening program management and developing strategic partnerships with the business and industrial sectors are important steps in improving the effectiveness of Teaching Factory implementation in schools.